Preparation of CdIn2S4/TiO2 Nanocomposites and Its Photocathodic Protection Properties for Q235 Carbon Steel - SONG Wei - zhe, LI Hong, CUI Xing - qiang, LI Yan - hui, CHENG Lian - jun, LI Jun - ru (Cailiao Baohu)
CdIn2S4/TiO2 nanocomposites were prepared by depositing CdIn2S4 on TiO2 nanotubes prepared by anodic oxidation via hydrothermal method to improve the photoelectric conversion efficiency of TiO2 and its photogenerated cathodic protection performance under visible light. Scanning electron microscopy (SEM), X - ray diffractometer (XRD), X - ray photoelectron spectroscopy (XPS) and UV - visible diffuse reflection spectra (UV - vis DRS) were used to analyze the surface morphology, crystal phase, elemental composition and light response characteristics of the prepared CdIn2S4/TiO2 nanocomposites, respectively. Open circuit potential (OCP), Tafel curve and electrochemical impedance spectroscopy (EIS) were tested to study the photogenerated cathodic protection performance of the composites for Q235 carbon steel. Results showed that CdIn2S4 flower clusters were successfully loaded on the surface of TiO2 nanotubes. Under visible light irradiation, the coupling of CdIn2S4/TiO2 nanocomposites could significantly reduce the OCP of Q235 carbon steel, and the value of the OCP of Q235 carbon steel coupled with CdIn2S4/TiO2 nanocomposites could reach -1.12 V (vs SCE), indicating that the combination of CdIn2S4 and TiO2 can significantly improve the photogenerated cathodic protection performance of TiO2 for Q235 carbon steel. This could be explained as follows: after depositing CdIn2S4, the response capability of TiO2 nanotubes to visible light was significantly enhanced, and the photoelectric conversion efficiency was significantly improved.